Psychosocial Support and Quality of Life in CKD Patients on Hemodialysis Amidst the Sudan Conflict: A Cross-Sectional Study - Ahmed MohammedAlhassan Ismail Abdulsamad; Ibrahim Nagmeldin Hassan; Mohamed Ibrahim (International Journal of Medical Students)
BACKGROUND: Chronic kidney disease (CKD) patients undergoing hemodialysis often experience significant physical and psychological challenges. The quality of life (QoL) for these patients is influenced by various factors, including psychosocial support (1). In conflict-affected regions like Sudan, the ongoing armed conflict has further complicated these challenges (2). This study aims to assess the impact of psychosocial support on the QoL of CKD patients on hemodialysis amidst the Sudan conflict and to evaluate how conflict-related disruptions affect their well-being.